Lattice NRQCD study of S- and P-wave bottomonium states in a thermal medium with Nf = 2 + 1 light flavors - Kim, Seyong; Petreczky, Peter; Rothkopf, Alexander (Physical review. D, Particles, fields, gravitation, and cosmology, 2015)
We investigate the properties of S- and P-wave bottomonium states in the vicinity of the deconfinement transition temperature. The light degrees of freedom are represented by dynamical lattice quantum chromodynamics (QCD) configurations of the HotQCD collaboration with Nf=2+1 flavors. Bottomonium correlators are obtained from bottom quark propagators, computed in nonrelativistic QCD under the background of these gauge field configurations. The spectral functions for the 3S1 (Υ) and 3P1 (χb1) channel are extracted from the Euclidean time correlators using a novel Bayesian approach in the temperature region 140 MeV≤T≤249 MeV and the results are contrasted to those from the standard maximum entropy method. We find that the new Bayesian approach is far superior to the maximum entropy method. It enables us to study reliably the presence or absence of the lowest state signal in the spectral function of a certain channel, even under the limitations present in the finite temperature setup. We find that χb1 survives up to T=249 MeV, the highest temperature considered in our study, and put stringent constraints on the size of the medium modification of Υ and χb1 states.